METODE DAKWAH DALAM PEMBINAAN NARAPIDANA DI LEMBAGA PERMASYARAKATAN KELAS II A BULUKUMBA (Jurnal Washiyah: Jurnal Kajian Dakwah dah Komunikasi, 2021)
The results showed that the form of training for prisoners at the Class II A Correctional Institution in Bulukumba was carried out in 3 forms, namely religious guidance, skills development and social coaching. And the da’wah method used in the Bulukumba Class II Correctional Institution uses more than one da’wah, namely the bil hikmah (wisdom) method through lectures, the mauizatil khazanah method through stories, and the al mujadalah method through question and answer and discussion.